Morpho-bathymetric features of the Southwest Celebes Sea - Tiranda, Herwin (Berita Sedimentologi, 2022)
The Southwest Celebes Sea lies within the region of Celebes Sea (also known locally as Sulawesi Sea)-Makassar Strait gateway which is controlled by active tectonic of North Sulawesi Trench and Palu-Koro Fault zone. In addition, this region is the major inter-ocean route of Indonesian Throughflow (ITF). Using the high-resolution multibeam bathymetry data supplemented with 2D seismic profiles, this study describes major morpho-bathymetric features that can be observed within the Southwest Celebes Sea. There are 4 types of morpho-bathymetric features: structural features, erosional features, gravitational features, and depositional features. The dominant structural related tectonic features and gravitational features mainly occur in the North Sulawesi Fold-Thrust Belt associated with the formation of the North Sulawesi Trench and Palu-Koro Fault zone. Whereas, to the northern part, the deeper area of the Celebes Sea and the region on the west are mainly controlled by erosional and depositional features.  The identification of morpho-bathymetric features provides useful information for basin analysis study and present-day or future offshore activities such as infrastructure engineering related to geohazard potential caused.